The social self and social death: Rethinking reparations for genocide and crimes against humanity - Marsoobian, A.T. (Pragmatism Today, 2020)
Based on a pragmatist inspired conception of the social self, the concept of reparations for the harms of genocide is reexamined. Both Raphael Lemkin, the person who invented the term “genocide,” and Claudia Card, a philosopher who examined the evil of genocide, hold similarly expansive notions of the harms inflicted by genocidal violence. Both argued that biological death is not necessarily central to genocide. For Lemkin cultural destruction of the targeted group is just as essential as the actual killing itself. Genocide is a group crime that aims to destroy the group and all the social aspects of group identity. Card similarly sees the target of genocidal violence as the social vitality of the self. This vitality is sustained by group relations. Reparations thus need to be reconceptualize in terms of the restoration of social life of the victim group and not solely on the basis of economic losses. Examples are given for the reparation of the social vitality of communities that have suffered genocide. © 2020 Central European Pragmatist Forum. All rights reserved.
Keywords: Claudia Card; Genocide; Raphael Lemkin; Reparations; Social death; Social self; dept.phi; peer-reviewed; ⛔ No DOI found

The Armenian Genocide of 1915: Armen T. Marsoobian explores the complex history of one of the 20th-century's worst and most neglected crimes against humanity - Marsoobian, A.T. (History Today, 2015)
Keywords: dept.phi; ⛔ No DOI found

Saying, singing, or semiotics: "Prima la musica e poi le Parole" revisited - Marsoobian, A.T. (Journal of Aesthetics and Art Criticism, 1996)
2 citations (Crossref) [2023-10-31]
Keywords: dept.phi

Why Controlling the Historical Narrative Matters: A Jamesian Response - Marsoobian, A.T. (Pragmatism Today, 2022)
An examination of the lessons learned from William James’s oration on the dedication of the Civil War Monument memorialization Colonel Robert Shaw and the Fifty-Fourth Regiment Massachusetts Infantry, an all-Black unit. The role of monuments in making visible the values of a society is explored in the context of promoting a nation’s historical narrative, in particular in their propagation of the South’s Lost Cause narrative. The genocidal violence against Armenians in the Caucasus by the Azerbaijani regime serves as the second illustration of the abuse of historical narratives. © 2022 Central European Pragmatist Forum. All rights reserved.
Keywords: Armenians; Azerbaijan; Civil War monuments; William James; civic courage; dept.phi; genocidal violence; historical narratives; peer-reviewed; the Lost Cause; ⛔ No DOI found

Aesthetics - Marsoobian, A.T. (The Bloomsbury Handbook of Pragmatism, 2024)
Keywords: dept.phi

Denialism and its consequences: the epistemic injustice of national narratives - Marsoobian, A.T. (Pragmatism Today, 2024)
An analysis of how national narratives are inevitably forms of epistemic injustice, depriving individuals of epistemic and moral agency. Denying access to knowledge about the past is a tool of all autocratic regimes, commonly used for the purpose of retaining power and exerting dominance over individuals or groups subordinate to the ruling elite. Yet such narratives and the falsifications used to buttress them, are not the exclusive instruments of autocracies but can be found to pervade the national narratives of what we often nominally label as democracies. The denial of crimes against humanity and genocide are the most egregious examples of the harms perpetrated against victims and survivors. Miranda Fricker’s writings on epistemic injustice are employed in the analysis. Turkish and Azerbaijani genocide denial of the Armenian Genocide are used to illustrate how epistemic injustice lies at the heart of denialism. © 2024 Central European Pragmatist Forum. All rights reserved.
Keywords: Melanie Altanian; Miranda Fricker; denialism; dept.phi; epistemic injustice; genocide; national narratives; peer-reviewed

Editors' Introduction - Lindert, J.; Marsoobian, A.T. (Multidiscipl. Perspect. on Genocide and Memory, 2018)
Journal Abbreviation: Multidiscipl. Perspect. on Genocide and Memory
Keywords: dept.phi